Is the European automotive industry ready for the global electric vehicle revolution? - Gustav Fredriksson; Alexander Roth; Simone Tagliapietra; Reinhilde Veugelers (Bruegel, 2018)
The automotive sector is currently at the centre of a global transformation, driven by four key trends: electrification, autonomous driving, sharing and connected cars. While each of these interconnected trends is already visible in daily life, their full deployment is not yet guaranteed, nor is the speed of take-up. This Policy Contribution investigates the position of the European automotive industry in a scenario in which electrification substantially progresses. The results are encouraging for Europe: EU companies entered the global electric vehicle race late, but on the basis of our analysis it is not yet too late for them to catch up and make the best of this change. European car manufacturers can rely on a large internal market, long experience in automotive manufacturing and a portfolio of research and development projects and patents that is diversified across various power-train technologies. But if Europe wants to succeed in the global electric vehicle race, its automotive industry will have to move into higher gear to meet the global - notably Chinese - competition. Nevertheless, industry needs the proper framework conditions as the basis for more ambitious investments in electrification - as examples such as Norway or China demonstrate. This Policy Contribution formulates a broad policy framework for deployment and production of electric vehicles in Europe, combining demand and supply-side instruments. Europe cannot follow China in the adoption of centrally-planned industrial policy measures. But it certainly can and should do more to stimulate the transformation of its automotive industry through more ambitious policies.
Keywords: 330